Audit Toolandlinkedarchivesystem(Atlas) User Behavior Analysis Using Technology Acceptance Model(Tam) - Martanto, Bayu Prayoga; Firmanto, Yuki (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study aims to explain the Audit Tool and Linked Archive System (ATLAS) user behavior through Technology Acceptance Model (TAM). This study employs explanatory method to explain user behavior, and includes 35 samples of both accounting students and public accounting firm auditors in Malang. The study results exhibit that there are positive effects of perceived ease of use on perceived usefulness, perceived ease of use on user behavior, user behavior on intention to use, perceived usefulness on intention to use, and intention to use on actual use. This study also finds that perceived usefulness has no positive effect on user behavior.